Genetic diversity assessment in pea cultivars and lines using the SSR analysis - K. P. Gainullina; B. R. Kuluev; F. A. Davletov (Труды по прикладной ботанике, генетике и селекции)
Background. Pea is the main leguminous crop in the Republic of Bashkortostan and widespread all over the world. The key role in the breeding of new pea cultivars is played by source material representing the phenotypic and genotypic diversity of Pisum sativum L., searched for in plant genetic resources collections. SSR markers are successfully used to study the DNA polymorphism of various genetic objects, including pea. However, the distribution of a number of microsatellite alleles in the genotypes of specific lines and cultivars of this valuable pulse crop remains practically unexplored.Materials and methods. Molecular genetic polymorphism was studied in 40 pea cultivar accessions of different ecological and geographical origin from the Vavilov Institute’s genebank of plant genetic resources or developed at regional breeding centers. Microsatellite analysis was performed using 5 SSR markers from the genomic library of microsatellites (Agrogene®, France).Results. All markers delivered good electrophoretic profiles and helped to amplify a number of alleles per locus varying from 2 (AB53) to 9 (AA355). The total number of alleles was 26, while the average number of alleles per locus was 5.2. The polymorphism information content (PIC) varied from 0.39 for locus AB53 to 0.82 for locus AA355, with the mean value of 0.60. The set of SSR markers used in the work made it possible to individualize each of the studied pea genotypes. The measured genetic distances were used to draw a dendrogram showing the distribution of genotypes according to their genetic relationship.Conclusion. Through studying the source material for pea breeding by the SSR analysis the data were obtained that provide additional information about the genetic structure of the collection and the polymorphism of the studied cultivar accessions. The results of genotyping pea cultivars and lines can be used for their genetic identification or to select parental pairs for hybridization.